Reaksi Pasar Terhadap Kebijakan Tax Amnesty Pada Saat Pengumuman, Periode I, Periode II, dan Periode III - Trisnayanti, Ni Putu Mediana; Noviari, Naniek (E-Jurnal Akuntansi; Vol 23 No 1 (2018), 2018)
The e purpose e of f this s study y was conducted in order to analyze the difference of abnormal return on LQ-45 stock before and after Tax Amnesty policy. Event study is a method used in this study, by observation or observation of the average abnormal return for 5 days before the event, event date, and 5 days after the announcement event, the period I, II, and III Tax Amnesty.  The secondary data used here is downloaded from IDX and Capital Market Data Center. The data used in this research is the closing stock price daily or closing price, LQ-45 stock index. The sample selected in this research is the shares of the companies listed in the LQ-45 list on the Indonesia Stock Exchange.  Based on the result of the research analysis, it is found that t ther ee is s an n abnormal l return difference before e and d after r Tax Amnesty announcement, but there e is s no o difference e of average abnorma ll return n before e and d after e period I, II, and d III Tax Amnesty due to lack of observation time.